1988
DOI: 10.1177/039139888801100309
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Biocompatibility of Two Different Dialysis Membranes: Cuprophane and Polysulfone

Abstract: Intradialytic hypoxemia, leukopenia and coagulation system activation were monitored in 9 uremic patients during hemodialysis with cuprophane (Cu) and polysulfone (Psf) membranes, using the following parameters: polymorphonuclear count (PMN), elastase alpha-1 proteinase inhibitor (EI-alpha 1PI) complex, platelet count, beta-thromboglobulin (BTG), fibronectin (FN) and arterial oxygen tension (PaO2). Our results indicate that 1) intradialytic hypoxemia observed with both membranes does not seem to be exclusively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…These findings would mean that the stimuli causing the degranulation of platelets persist longer than the stimuli causing the conformational activation of GPIIb/IIIa during hemodialysis. Platelet activation during hemodialysis may be due to many factors, including shear stress, contact activation and agonist activation [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. Further examination is still needed to elucidate the more precise mechanism of platelet activation during hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings would mean that the stimuli causing the degranulation of platelets persist longer than the stimuli causing the conformational activation of GPIIb/IIIa during hemodialysis. Platelet activation during hemodialysis may be due to many factors, including shear stress, contact activation and agonist activation [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. Further examination is still needed to elucidate the more precise mechanism of platelet activation during hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…During hemodialysis, the contact of blood with the prosthetic devices and the interaction of blood and artificial membranes result in platelet activation and a decrease in platelet cell count [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. The degree of platelet activation depends on the flow design of the dialysis membrane used [1, 2], the composition and geometry of the dialysis membrane [3, 4, 5, 6, 7, 8, 9, 10], and on rheological factors derived from blood circulation [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although acute leukopenia is known to occur in all patients during the first 30 min of HD treatment [10], our study showed no reduction in the WBC during dialysis with either dialyzer. The platelet count usually decreases 5 to 15% at 15 to 30 min from the start of HD and recovers to the normal level by the end of the dialysis session [9,11]. Oshihara [3] reported that the numbers of platelets adhering to the membrane surface were lower with NV than with the conventional PS (CX) membrane.…”
Section: Ns Not Significantmentioning
confidence: 99%